ANALISIS MANAJEMEN SEKOLAH DASAR AISYIYAH BERBASIS AL-QURAN - Muhdan Amin (LPPM Universitas Cipta Mandiri, 2024)
School management is an important factor in the implementation of education and teaching in schools. The success of school management is measured by the achievements obtained by students. Therefore, in preparing school management, there needs to be involvement from various components such as teachers, staff, parents and the community. School management is an important thing that must be done so that the school can achieve learning goals well. This research uses a qualitative method, this is because the author tries to explain the school management carried out at Aisyiyah Elementary School based on the Al-Quran. The results of the research show that in its efforts to create students who are in line with the educational goals at SD Aisyiyah Sukabumi, SD Aisyiyah carries out school management which includes curriculum management, human resource management, infrastructure management, financial management and management of students' parents.